2010
DOI: 10.1093/jac/dkp503
|View full text |Cite
|
Sign up to set email alerts
|

Binding of ceftaroline to penicillin-binding proteins of Staphylococcus aureus and Streptococcus pneumoniae

Abstract: The high affinities of ceftaroline for MRSA PBP2a, MSSA PBPs 1-3 and S. pneumoniae PBP2x/2a/2b support the potential efficacy of ceftaroline in the treatment of infections caused by MRSA and S. pneumoniae.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(108 citation statements)
references
References 12 publications
6
101
0
1
Order By: Relevance
“…All antibiotics tested had a weak affinity for PBP4 (IC 50 Ͼ 8 g/ml). Moisan et al observed similar weak affinities of ceftaroline and ceftriaxone for PBP4 in strain ATCC 29213 (42). A fluorogram of PBP resolutions in methicillin-susceptible S. aureus ATCC 29213 is presented in Fig.…”
Section: Vol 54 2010 Ceftaroline Affinity For Gram-positive Pbps 1671mentioning
confidence: 79%
See 1 more Smart Citation
“…All antibiotics tested had a weak affinity for PBP4 (IC 50 Ͼ 8 g/ml). Moisan et al observed similar weak affinities of ceftaroline and ceftriaxone for PBP4 in strain ATCC 29213 (42). A fluorogram of PBP resolutions in methicillin-susceptible S. aureus ATCC 29213 is presented in Fig.…”
Section: Vol 54 2010 Ceftaroline Affinity For Gram-positive Pbps 1671mentioning
confidence: 79%
“…Previous papers using comparable techniques reported average IC 50 s of 0.16 to 0.9 g/ml for ceftaroline in MRSA strains (27,42,64). Differences between our results and those reported previously (27) may be explained at least partially by differences in strains and culture conditions.…”
Section: Vol 54 2010 Ceftaroline Affinity For Gram-positive Pbps 1671mentioning
confidence: 90%
“…Van-BDP has been used extensively to detect the location of peptidoglycan synthesis in Gram-positive bacteria (9,14,17,31,39,54). Bocillin FL is a fluorescent penicillin V derivative that binds tightly to penicillin binding proteins (PBPs) (35,59). In control cultures (without daptomycin), Van-BDP intensely stained both complete and incomplete septa and only faintly stained the sidewalls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…64 Ceftaroline has antimicrobial activity against MDR Gram-positive bacteria including S. aureus and S. pneumoniae and has up to 256-fold higher affinity for PBP2a than traditional cephalosporins. 65 Interestingly, unhydrolyzed ceftaroline was found to mimic the allosteric activation of PBP2a by PG and promote acylation by a second ceftaroline molecule in the active site [ Fig. 4(B)].…”
mentioning
confidence: 99%